Is a reduction in viability enough to determine biofilm susceptibility to a biocide?. (2nd December 2021) - Ledwoch, Katarzyna; Magoga, Maddalena; Williams, Dulcie; Fabbri, Stefania; Walsh, James; Maillard, Jean-Yves
Abstract: Objective: The abundance and prevalence of dry-surface biofilms (DSBs) in hospitals constitute an emerging problem, yet studies rarely report the cleaning and disinfection efficacy against DSBs. Here, the combined impact of treatments on viability, transferability, and recovery of bacteria from DSBs has been investigated for the first time. Methods: Staphylococcus aureus DSBs were produced in alternating 48-hour wet–dry cycles for 12 days on AISI 430 stainless steel discs. The efficacy of 11 commercially available disinfectants, 4 detergents, and 2 contactless interventions were tested using a modified standardized product test. Reduction in viability, direct transferability, cross transmission (via glove intermediate), and DSB recovery after treatment were measured. Results: Of 11 disinfectants, 9 were effective in killing and removing bacteria from S. aureus DSBs with >4 log10 reduction. Only 2 disinfectants, sodium dichloroisocyanurate 1, 000 ppm and peracetic acid 3, 500 ppm, were able to lower both direct and cross transmission of bacteria (<2 compression contacts positive for bacterial growth). Of 11 disinfectants, 8 could not prevent DSB recovery for >2 days. Treatments not involving mechanical action (vaporized hydrogen peroxide and cold atmospheric plasma) were ineffective, producing <1 log10 reduction in viability, DSB regrowth within 1 day, and 100% transferability of DSB after treatment. Conclusions: Reduction in bacterial viability alone does not determine product performance against biofilm and might give a false sense of security to consumers, manufacturers and regulators. The ability to prevent bacterial transfer and biofilm recovery after treatment requires a better understanding of the effectiveness of biocidal products.